Screening of the UV absorption capacity, proximal and chemical characterization of extracts, and polysaccharide fractions of the Gracilariopsis tenuifrons cultivated in Colombia - Yessica Monsalve-Bustamante, Stefanie Rincón-Valencia, Juan Mejía-Giraldo&, Diego Moreno-Tirado, Miguel Puertas-Mejía (Journal of Applied Pharmaceutical Science, 2019)
The sustainable use of marine resources is a competitive advantage of the most developed countries, which has a positive impact on the economic and social development of their populations. Currently, marine organisms such as macroalgae are an important source of functional compounds such as polysaccharides, proteins, unsaturated and polyunsaturated fatty acids, among others, with nutritional value and pharmacological properties. Gracilariopsis tenuifrons is a macroalga found in the Colombian Caribbean Sea, which has been neither chemically nor physicochemically studied; therefore, the aim of this study was to evaluate the polysaccharides composition and nutrients contents of crude extract and its UV radiation absorption capacity. The purification was carried out by ultrafiltration using membranes of molecular size exclusion 100, 50, 10, and 3 kDa. The chemical characterization was done by gel electrophoresis, Nuclear Magnetic Resonance, Fourier Transform Infrared Spectroscopy, and the particle size and potential zeta by Dynamic Light Scattering. The absorption coefficient (absorbance/g dry sample) was measured at 290, 310, 340, and 380 nm. Sulfated and non-sulfated polysaccharides were detected in the fractions and identified as polysaccharides type k, and β-carrageenan and alginate. The proximate analysis showed that the total content of protein, carbohydrates, fat, and calories is 15.58%, 69.81%, 0.15%, and 342.94% Kcal, respectively. The crude extracts showed an important absorption coefficient in UVB-UVA range. The findings suggest that G. tenuifrons seaweed propagated in vitro is a viable candidate of natural additives, such as phycocolloids and bioactive compounds, for designing new functional products in the pharmaceutical and cosmetic industry, in addition to its nutritional properties to be used in foods.
Keywords: Algae, chemical characterization, Colombian red seaweed, Gracilariopsis tenuifrons, polysaccharides, UV radiation absorption.